Green self-compacting field polymer concrete and preparation method thereof

By using green self-solid ground polymer concrete with calcined copper tailings powder, slag and fly ash as cementitious materials, the existing ground polymer concrete has low fluidity and low compressive resistance, and the effects of high fluidity and high compressive strength have been achieved, and the disadvantages such as high brittleness and easy alkali resistance have been overcome.

CN119750977AInactive Publication Date: 2025-04-04NORTH CHINA UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202510251860.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyconcrete has low fluidity and low compressive resistance, so it cannot effectively use the steel pipe constraints to enhance the strength and ductility of the concrete. At the same time, the internal concrete cannot improve the stability of the steel pipe, avoid or delay premature yield of the steel pipe.

Method used

Calcined copper tailings powder, slag and fly ash are used to replace traditional cement as cementitious materials to prepare a green self-solid ground polymer concrete and fill it into steel pipes to improve the flowability, compactness and strength of the concrete.

Benefits of technology

It has achieved the advantages of green and environmental protection, improved the fluidity and compressive strength of concrete, overcome the disadvantages of high brittleness and easy alkali resistance of ground polymer concrete, and fully utilized the advantages of concrete and steel pipes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750977A_ABST
    Figure CN119750977A_ABST
Patent Text Reader

Abstract

The invention provides green self-compacting field polymer concrete and a preparation method thereof, and relates to the technical field of building materials. The green self-compacting polymer concrete provided by the invention is prepared from the following raw materials: calcined copper tailing powder, slag, fly ash, an alkali activator, machine-made sand, gravel, additional water, a water reducing agent and a retarder. The calcined copper tailing powder, the slag and the fly ash are adopted to completely replace traditional cement to serve as a cementing material, emission of carbon dioxide in the concrete production process is reduced, meanwhile, the pollution problem generated by solid waste is solved, and the environment-friendly effect is achieved; the activity of the concrete can be improved through the calcined copper tailing powder, the fluidity of the concrete can be improved through the calcined copper tailing powder so as to achieve the self-compacting purpose, meanwhile, gaps between aggregates can be better filled, a better bonding effect is achieved, and the fluidity, compactness and strength of the concrete can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a green self-compacting polymer concrete and a preparation method thereof. Background Art

[0002] Concrete is one of the most important building materials at present. It is made of cementitious materials, aggregates, water, and admixtures and additives added in a certain proportion, mixed evenly, and compacted. In recent years, scholars and engineers at home and abroad have begun to explore the application of solid waste in concrete to realize the resource utilization of solid waste. Through reasonable proportions and preparation processes, solid waste can be used as concrete raw materials to replace some traditional building materials such as cement and aggregates. This not only helps to reduce the accumulation of solid waste and environmental pollution, but also reduces the production cost of concrete, achieving a win-win situation of economic and environmental benefits.

[0003] Geopolymer concrete is a new type of concrete material, which is a mixture of cement, sand, gravel, mineral materials rich in silica and alumina, and alkali activators. However, geopolymer concrete often has disadvantages such as high brittleness and easy alkali reaction. In order to expand the application scope of geopolymer materials, steel pipes can be combined with geopolymer concrete to form a composite structure. However, the existing geopolymer concrete has low fluidity and low compressive resistance. It cannot make good use of the restraining effect of steel pipes to enhance the strength and ductility of geopolymer concrete. At the same time, the internal geopolymer concrete cannot improve the stability of steel pipes well, avoid or delay the premature yield of steel pipes. Therefore, it is necessary to design a green self-compacting geopolymer steel tube concrete with high fluidity and good strength, give full play to the advantages of concrete and steel pipes, solve the problems of environmental pollution and solid waste resource treatment, and promote the development of the building materials industry at the same time, and achieve a win-win situation of economic benefits and environmental benefits. Summary of the invention

[0004] The purpose of the present invention is to provide a green self-compacting polymer concrete and a preparation method thereof. The green self-compacting polymer concrete provided by the present invention uses solid wastes such as slag, fly ash and calcined copper tailings powder as raw materials, saves resources, and is green and environmentally friendly; at the same time, it has excellent strength and fluidity, and when filled into a steel pipe, it can largely make up for the disadvantages of geopolymer concrete such as easy alkali reaction and high brittleness.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A green self-compacting polymer concrete, comprising the following raw materials in parts by weight: 403-497 parts of cementitious materials, 178.02-226.98 parts of alkali activator solution, 618-636 parts of machine-made sand, 927-954 parts of crushed stone, 48.79-94.09 parts of added water, 18-36 parts of water reducing agent solution, and 13.5-22.5 parts of retarder; the cementitious materials include calcined copper tailings powder, slag and fly ash.

[0006] Preferably, the mass fraction of the calcined copper tailings powder is 27-54 parts, the mass fraction of the slag is 216-243 parts, and the mass fraction of the fly ash is 160-200 parts.

[0007] Preferably, the preparation method of the calcined copper tailings powder comprises: drying and grinding the copper tailings in sequence to obtain the ground copper tailings; calcining the ground copper tailings to obtain the calcined copper tailings powder; the particle size of the ground copper tailings is not higher than 0.074 mm; the calcination temperature is 700~1000°C, the insulation time is 60~90min, and the heating rate to the calcination temperature is 5~10°C / min.

[0008] Preferably, the modulus of the alkaline activator solution is 1 to 1.4.

[0009] Preferably, the preparation method of the alkaline activator solution comprises: adding a sodium hydroxide solution into a water glass solution to obtain the alkaline activator solution; the concentration of the sodium hydroxide solution is 10-14 mol / L.

[0010] Preferably, the water glass solution has an initial modulus of 3.10-3.40, a solid content of 34%-36%, and a Baume degree of 38-41°Bé.

[0011] Preferably, the machine-made sand is medium sand with a fineness modulus of 2.3-3.0; the crushed stone is natural crushed stone with a particle size of 5-16 mm; the fly ash is Class I fly ash with a particle size not higher than 0.074 mm; and the slag is Class S95 slag with a particle size not higher than 0.074 mm.

[0012] Preferably, the water-reducing agent solution is a polycarboxylic acid high-performance water-reducing agent solution, the water reduction rate of the polycarboxylic acid high-performance water-reducing agent solution is 26% to 30%, the air content is 4.0% to 5.5%, and the solid content is 38.5% to 41%; the retarder is sucrose.

[0013] The present invention also provides a method for preparing the green self-compacting polymer concrete, comprising the following steps: Mixing cementitious materials, crushed stone and machine-made sand to obtain a solid mixture; The solid mixture, alkali activator solution, water reducing agent solution, retarder and added water are mixed to obtain the green self-compacting polymer concrete.

[0014] The present invention also provides a steel tube concrete column, comprising a steel tube and green self-compacting polymer concrete filled inside the steel tube; The green self-compacting polymer concrete is the green self-compacting polymer concrete described in the above technical solution or the green self-compacting polymer concrete prepared by the preparation method described in the above solution.

[0015] Beneficial effects: The invention provides a green self-compacting polymer concrete, comprising the following raw materials in parts by mass: 403-497 parts of cementitious materials, 178.02-226.98 parts of alkali activator solution, 618-636 parts of machine-made sand, 927-954 parts of crushed stone, 48.79-94.09 parts of added water, 18-36 parts of water reducing agent solution, and 13.5-22.5 parts of retarder; the cementitious materials comprise calcined copper tailings powder, slag and fly ash. The present invention adopts calcined copper tailing powder, slag and fly ash to completely replace traditional cement as cementitious materials to prepare geopolymer concrete, thereby reducing the emission of carbon dioxide in the concrete production process, solving the pollution problem caused by solid waste, and having the advantages of being green and environmentally friendly; moreover, the calcined copper tailing powder provides silicon, aluminum and oxygen elements for the cementitious material, and under the action of an alkali activator, forms a three-dimensional network space structure with slag and fly ash, improves the fluidity of the concrete to achieve the purpose of self-compacting, and can better fill the gaps between aggregates, play a better bonding role, and can improve the fluidity, density and strength of the concrete.

[0016] The geopolymer concrete provided by the present invention has good fluidity and compressive strength, and the preparation method is simple and easy, and is easy to promote and apply in engineering projects; the geopolymer concrete prepared by the present invention is combined with a steel pipe to give full play to the advantages of the good fluidity, high compressive strength, green environmental protection and good ductility of the steel pipe, and overcome the disadvantages of the geopolymer concrete such as high brittleness and easy alkali reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0018] Figure 1 Schematic diagram of the process for preparing green self-compacting polymer concrete; Figure 2 This is the full cycle change diagram of specimen GCSTB-A2 from loading to failure. DETAILED DESCRIPTION

[0019] The present invention provides a green self-compacting polymer concrete, comprising the following raw materials in parts by weight: 403-497 parts of cementitious materials, 178.02-226.98 parts of alkali activator solution, 618-636 parts of machine-made sand, 927-954 parts of crushed stone, 48.79-94.09 parts of added water, 18-36 parts of water reducing agent solution, and 13.5-22.5 parts of retarder; the cementitious materials include calcined copper tailings powder, slag and fly ash.

[0020] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0021] In terms of mass fraction, the raw materials for preparing the green self-compacting polymer concrete provided by the present invention include 403 to 497 parts of cementitious materials, specifically 420 parts, 450 parts, 480 parts or 490 parts. In the present invention, the gel generated by the cementitious materials during the hydration process can be filled into the pores inside the concrete, including the gaps between particles and the interface pores between aggregates and slurry, etc. This filling effect makes the concrete more compact, reduces the porosity, and thus improves the strength and durability of the concrete.

[0022] In the present invention, the cementitious material includes calcined copper tailing powder, slag and fly ash. The calcined copper tailing powder partially replaces slag and fly ash as cementitious materials, slag provides early strength, calcined copper tailing powder and fly ash improve concrete fluidity, and the three as cementitious materials play a bonding role; copper tailing powder, slag and fly ash all replace traditional cement as cementitious materials to prepare geopolymer concrete, which reduces the emission of carbon dioxide in the concrete production process, and solves the pollution problem caused by solid waste, and has the advantages of green environmental protection.

[0023] In the present invention, the mass fraction of the calcined copper tailings powder is preferably 27 to 54 parts, specifically 30 parts, 40 parts or 50 parts; the mass fraction of the slag is preferably 216 to 243 parts, specifically 220 parts, 230 parts or 240 parts; the mass fraction of the fly ash is preferably 160 to 200 parts, specifically 170 parts, 180 parts or 190 parts.

[0024] In the present invention, the preparation method of the calcined copper tailings powder preferably includes: drying and grinding the copper tailings in sequence to obtain the ground copper tailings; calcining the ground copper tailings to obtain the calcined copper tailings powder; the particle size of the ground copper tailings is preferably not higher than 0.074 mm, specifically not higher than 0.050 mm, not higher than 0.010 mm or not higher than 0.005 mm; the calcination conditions preferably include: a temperature of 700-1000°C, specifically 750°C, 800°C or 900°C, a holding time of 60-90 min, specifically 65 min, 70 min or 80 min, and a heating rate of 5-10°C / min to the calcination temperature, specifically 6°C / min, 7°C / min or 8°C / min.

[0025] In the present invention, the fly ash is preferably Class I fly ash, and the particle size is preferably not higher than 0.074 mm, specifically not higher than 0.050 mm, not higher than 0.010 mm or not higher than 0.005 mm; the slag is Class S95 slag, and the particle size is not higher than 0.074 mm, specifically not higher than 0.050 mm, not higher than 0.010 mm or not higher than 0.005 mm.

[0026] Based on the mass fraction of the cementitious material, the raw materials for preparing the green self-compacting polymer concrete provided by the present invention also include 178.02 to 226.98 parts of an alkali activator solution, specifically 180 parts, 202.5 parts, 210 parts or 220 parts. In the present invention, the alkali activator solution catalyzes the cementitious material. The alkali activator solution in the present invention can destroy the chemical bonds (such as Si-O-Si bonds, Al-O-Al bonds, Si-O-Al bonds, etc.) in the cementitious material by providing an alkaline environment, so that the active ingredients (such as SiO 2 and Al 2 O 3 ) is in a free state, forming highly active, unsaturated chemical bonds, which accelerates the hydration reaction rate of the cementitious material, allowing the semi-crystalline or amorphous siliceous-aluminous material to be quickly converted into a three-dimensional inorganic network polymer, while promoting the formation of minerals such as low-calcium silicates, aluminates, and aluminosilicate gels, thereby improving the early strength of the cementitious material.

[0027] In the present invention, the modulus of the alkaline activator solution is preferably 1-1.4, specifically 1.1, 1.2 or 1.3.

[0028] In the present invention, the preparation method of the alkaline activator solution preferably comprises: adding a sodium hydroxide solution to a water glass solution to obtain the alkaline activator solution; the concentration of the sodium hydroxide solution is 10-14 mol / L, specifically 11 mol / L, 12 mol / L or 13 mol / L.

[0029] In the present invention, after the sodium hydroxide solution is added to the water glass solution, it is preferably stirred for 5 to 7 minutes and allowed to stand at room temperature for 24 hours, and sealed with a plastic film during the standing time.

[0030] In the present invention, the preparation method of the sodium hydroxide solution preferably comprises: dissolving sodium hydroxide particles in water, cooling to room temperature, and sealing with plastic wrap to obtain the sodium hydroxide solution; the purity of the sodium hydroxide is preferably AR analytical grade. In the present invention, the sodium hydroxide solution can adjust the modulus of the water glass solution to prepare the alkali activator solution.

[0031] In the present invention, the initial modulus of the water glass solution is preferably 3.10-3.40, the solid content is preferably 34%-36%, and the Baume degree is preferably 38-41°Bé.

[0032] Based on the mass fraction of the cementitious material, the raw materials for preparing the green self-compacting polymer concrete provided by the present invention also include 618 to 636 parts of machine-made sand, specifically 620 parts, 627 parts or 630 parts.

[0033] In the present invention, the machine-made sand is used as a fine aggregate to fill concrete, which can improve the density of concrete. In the present invention, the machine-made sand is preferably medium sand, and the fineness modulus is preferably 2.3 to 3.0, specifically 2.4, 2.6, 2.7 or 2.9; Based on the mass fraction of the cementitious material, the raw materials for preparing the green self-compacting polymer concrete provided by the present invention also include 927 to 954 parts of crushed stone, specifically 930 parts, 940.5 parts or 950 parts.

[0034] In the present invention, the crushed stone is used as the coarse aggregate of concrete and the concrete is used as the skeleton of concrete, which can improve the strength of concrete. In the present invention, the crushed stone is preferably natural crushed stone, and the particle size is preferably 5-16 mm. In the present invention, the crushed stone is preferably continuously graded crushed stone, specifically including first crushed stone and second crushed stone; the particle size of the first crushed stone is 10-16 mm, and the particle size of the second crushed stone is 5-10 mm; the mass fraction of the first crushed stone in the continuously graded crushed stone is preferably 50%-60%, and the mass fraction of the second crushed stone is preferably 40%-50%.

[0035] Based on the mass fraction of the cementitious material, the raw materials for preparing the green self-compacting polymer concrete provided by the present invention further include 48.79 to 94.09 parts of added water, specifically 48.79 parts, 71.39 parts or 94.09 parts. In the present invention, the water-cement ratio of the green self-compacting polymer steel tube concrete is preferably 0.4 to 0.5, specifically 0.42, 0.45, or 0.47.

[0036] Based on the mass fraction of the cementitious material, the raw materials for preparing the green self-compacting polymer concrete provided by the present invention also include 18 to 36 parts of a water reducing agent solution, specifically 20 parts, 27 parts or 30 parts.

[0037] In the present invention, the water reducing agent solution can improve the fluidity, strength and durability of concrete and reduce engineering costs. In the present invention, the water reducing agent solution is preferably a polycarboxylic acid high-performance water reducing agent solution, and the water reduction rate of the polycarboxylic acid high-performance water reducing agent solution is preferably 26% to 30%, specifically 28% or 29%, the air content is preferably 4.0% to 5.5%, specifically 4.7% or 4.8%, and the solid content is preferably 38.5% to 41%, specifically 39.5% or 40.5%; the retarder is sucrose.

[0038] Based on the mass fraction of the cementitious material, the raw materials for preparing the green self-compacting polymer concrete provided by the present invention further include 13.5 to 22.5 parts of a retarder, specifically 15 parts, 15.75 parts or 20 parts; the retarder is preferably sucrose, and the sucrose is preferably analytically pure sucrose particles. In the present invention, the water reducer can slow down the setting time of concrete and improve the working performance.

[0039] The present invention also provides a method for preparing the green self-compacting polymer concrete, comprising the following steps: Mixing cementitious materials, crushed stone and machine-made sand to obtain a solid mixture; The solid mixture, alkali activator solution, water reducing agent solution, retarder and added water are mixed to obtain the green self-compacting polymer concrete.

[0040] Figure 1 The present invention is a schematic diagram of the process of preparing green self-compacting polymer concrete.

[0041] The present invention mixes the cementitious material, crushed stone and machine-made sand (referred to as the first mixing) to obtain a solid mixture. In the present invention, the first mixing is preferably stirring mixing, the first mixing time is preferably 2 minutes to 3 minutes, and the first mixing is preferably performed in a mixer.

[0042] After obtaining the solid mixture, the present invention mixes the solid mixture, alkali activator solution, water reducing agent solution, retarder and added water (referred to as the second mixing) to obtain the green self-compacting polymer steel tube concrete. In the present invention, the time of the second mixing is preferably 7 minutes to 9 minutes.

[0043] The present invention also provides a steel tube concrete column, comprising a steel tube and green self-compacting polymer concrete filled inside the steel tube; The green self-compacting polymer concrete is the green self-compacting polymer concrete described in the above technical solution or the green self-compacting polymer concrete prepared by the preparation method described in the above solution.

[0044] The present invention adopts calcined copper tailing powder, slag and fly ash to replace traditional cement as cementitious materials to prepare geopolymer concrete, which reduces the emission of carbon dioxide in the concrete production process and is green and environmentally friendly; at the same time, the addition of calcined copper tailing powder can improve the fluidity, density and strength of concrete. The geopolymer concrete provided by the present invention has good fluidity and compressive strength. Filling it into a steel pipe can give full play to the advantages of good fluidity, high compressive strength, green environmental protection and good ductility of the steel pipe, and overcome the disadvantages of geopolymer concrete such as high brittleness and easy alkali reaction.

[0045] In order to further illustrate the present invention, the green self-compacting polymer concrete and the preparation method thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0046] The crushed stone used in the embodiment of the present invention is continuously graded crushed stone, and the specific grading method is as follows: natural crushed stone is screened to obtain first crushed stone and second crushed stone; wherein the particle size of the first crushed stone is 10-16 mm, and the particle size of the second crushed stone is 5-10 mm; the first crushed stone and the second crushed stone are continuously graded according to a mass ratio of 6:4.

[0047] The calcined copper tailings powder used in the embodiment of the present invention is obtained by calcining copper tailings; the preparation method of the calcined copper tailings powder is preferably: grinding the copper tailings to a particle size not higher than 0.074 mm to obtain copper tailings powder, calcining in a box-type electric furnace, setting the calcination temperature to 800°C, the insulation time to 80min, the heating rate to the calcination temperature to 8°C / min, and naturally cooling to room temperature to obtain calcined copper tailings powder.

[0048] The water reducing agent solution used in the embodiment of the present invention is a polycarboxylic acid high-performance water reducing agent solution, with a water reduction rate of 28%, an air content of 4.7%, and a solid content of 39.5%, and the retarder is sucrose.

[0049] Example 1 A green self-compacting polymer concrete, the preparation method of which is as follows: Preparation of alkaline activator: AR analytical pure granular sodium hydroxide is prepared into a 12 mol / L NaOH solution, and the prepared NaOH solution is added dropwise into water glass (sodium silicate) with an initial modulus of 3.3, a solid content of 35.84%, and a Baume degree of 38.5°Bé, and the modulus is adjusted to 1.0 by stirring for 6 min. The mixture is allowed to stand at room temperature for 24 h, and sealed with a plastic film to obtain the alkaline activator.

[0050] The calcined copper tailings powder, slag, fly ash, machine-made sand and natural crushed stone were mixed according to the raw material ratio, and fully stirred for 3 minutes to obtain a solid mixture. The prepared alkali activator solution, water reducer solution and retarder were then added, mixed with water and fully stirred for 8 minutes to obtain a green self-compacting polymer concrete. The amount of each raw material is shown in Table 1.

[0051] Embodiment 2~6 The difference between Examples 2 to 6 and Example 1 is that the raw material ratios are different, see Table 1 below.

[0052] Table 1 Raw material ratios of Examples 1 to 6

[0053] Test Example 1 The green self-compacting polymer concrete obtained in Examples 1 to 6 was cured in a standard curing manner, and its expansion and compressive strength were tested. The results are shown in Table 2 below.

[0054] Table 2 Expansion and compressive strength of Examples 1 to 6

[0055] By comparing Examples 1 to 6, it can be seen that the green self-compacting polymer concrete obtained by the present invention has an expansion degree between 480 and 645 mm, a good slump expansion degree, a flowability that can reach the self-compacting standard, and good compressive strength.

[0056] By comparing Examples 1 to 3, when the calcined copper tailings powder accounts for about 10% of the slag, the water-cement ratio in Example 1 is 0.4, the alkali activator modulus is 1.0, and the resulting concrete has good compressive strength at 3d, 7d, and 28d, and the 28d compressive strength can reach 44.94MPa, but the slump expansion is 480mm; the water-cement ratio in Example 2 is 0.45, the alkali activator modulus is 1.2, and the slump expansion is 565mm. The compressive strength of the resulting concrete at 3d, 7d, and 28d is not significantly reduced compared with the compressive strength of Example 1, and the 28d compressive strength can reach 43.99MPa; the water-cement ratio of Example 3 is 0.5, the alkali activator modulus is 1.4, and the resulting concrete expansion reaches 560mm, but its 3d, 7d, and 28d compressive strengths are reduced compared with Examples 1 to 2, and the 28d compressive strength is 37.78Mpa. Therefore, Example 2 is a preferred raw material ratio when the calcined copper tailings powder accounts for about 10% of the slag. The water-binder ratio of Example 2 of the present invention is 0.45, the alkali activator modulus is 1.2, and the 28d compressive strength can reach 43.99MPa, which has good fluidity and compressive strength.

[0057] By comparing Examples 4 to 6, when the proportion of calcined copper tailings powder to slag is 20%, the water-cement ratio in Example 6 is 0.4, the alkali activator modulus is 1.4, and the obtained concrete has good compressive strength at 3d, 7d, and 28d, and the 28d compressive strength can reach 43.89MPa, but the slump expansion is 530mm; the water-cement ratio in Example 4 is 0.45, the alkali activator modulus is 1.0, the slump expansion of the obtained concrete reaches 630mm, and the 3d, 7d, and 28d compressive strengths are not significantly reduced compared with the compressive strength of Example 6, and the 28d compressive strength can reach 41.7MPa; the water-cement ratio in Example 5 is 0.5, the alkali activator modulus is 1.2, and the slump expansion of the obtained concrete reaches 645mm, but compared with Examples 4 and 6, its 3d, 7d, and 28d compressive strengths are reduced, and the 28d compressive strength is 32.68Mpa. Therefore, when the calcined copper tailings powder accounts for about 20% of the slag, Example 4 is the preferred raw material ratio. The water-binder ratio of Example 4 of the present invention is 0.45, the alkali activator modulus is 1.0, and the obtained concrete expansion reaches 630mm, and the 28d compressive strength is 41.7MPa, which has good fluidity and compressive strength.

[0058] The remaining embodiments are selected based on actual and engineering needs.

[0059] Test Example 2 Geopolymer concretes of Example 5 and Example 2 with strengths of C30 and C40, respectively, were selected and poured into steel pipes to test the compressive strength of geopolymer concrete in steel pipes. Among them, the steel pipe of Example 2 is numbered GCSTA, and the steel pipe of Example 5 is numbered GCSTB.

[0060] The test design produces a green self-compacting polymer concrete composite structure. The test parameters are the green self-compacting polymer concrete strength, cross-sectional dimensions, and steel pipe wall thickness, as shown in Table 3 below.

[0061] Table 3 Specimen design

[0062] Note: The test parameters are: geopolymer concrete strength, cross-sectional dimensions, and steel pipe wall thickness. Taking GCSTA-A1 as an example, GCST stands for green self-compacting polymer concrete, the first A stands for geopolymer concrete of different strengths; the second A stands for different cross-sectional dimensions; and 1 stands for different steel pipe wall thicknesses.

[0063] Figure 2The graph of the full cycle change of the specimen GCSTB-A2 from loading to failure is presented. The microscopic data of the test points in the test are connected with the macroscopic phenomena of the specimen and analyzed. At the beginning of loading, the specimen is in the elastic stage, that is, the OA section of the curve, and the appearance of the specimen does not change significantly. When it reaches point A, the longitudinal compression deformation of the specimen increases with the increase of load. At this time, the Poisson's ratio of the steel is greater than that of the concrete in the core area. The steel pipe mainly bears the pressure, and the strain of the steel pipe changes almost linearly with the load. Then it enters the AB section elastic-plastic stage, the load growth rate slows down, and when the ultimate load of the steel pipe at point B is reached, the steel pipe yields. As the load continues to increase gradually, the bearing capacity of the specimen decreases, the strain of each measuring point changes nonlinearly, and a slight bulge occurs at the end of the specimen. The load is gradually transferred from the steel pipe to the internal core area concrete, that is, reaching point C. Then the specimen entered the strengthening stage, and the bearing capacity gradually increased. At this time, the Poisson's ratio of concrete was greater than that of the steel pipe. The concrete in the inner core area mainly bore the axial load, and the bulging developed from the end to the middle. The deformation of the steel pipe gradually intensified, and the bearing capacity of the specimen was further improved, that is, the CD section of the curve.

[0064] During the test, the macroscopic performance of all specimens under axial load was not much different, and the failure phenomena of specimens with different geopolymer concrete strength grades were similar. The specimens were loaded in full cross section during the loading process to ensure that the steel pipe and the core area concrete were under pressure together. The failure phenomena of all specimens were similar, and the failure modes can be divided into elastic stage, elastoplastic stage, yield stage, and strengthening stage.

[0065] The axial compression performance of copper tailings geopolymer concrete-steel tube composite structure columns was tested on different specimens, and the results are shown in Table 4 below.

[0066] Table 4 Characteristic loads and characteristic displacements of different specimens

[0067] The characteristic load and characteristic displacement analysis of different specimens shows that: Due to the addition of geopolymer concrete, the bearing capacity of all specimens can be maintained at a high level. The steel pipe and geopolymer concrete share the load, giving full play to the complementary advantages and synergistic work of the two.

[0068] The improvement of concrete strength is conducive to the development of specimen yield displacement and peak load. Improving the strength of geopolymer concrete is conducive to the growth of peak load and the development of yield displacement.

[0069] The influence of cross-sectional dimensions on the characteristic load of the specimen is more prominent than that of the steel tube wall thickness. On the premise of meeting the design requirements, giving priority to appropriately increasing the cross-sectional dimensions can quickly improve the overall bearing performance of the structure.

[0070] The specimens obtained by the present invention have excellent deformation capacity. The calculated values ​​of the ductility coefficients of all specimens are between 13.37 and 31.48, with an average value of 19.85. The structure has relatively excellent bearing performance and deformation capacity under load. The deformation development of the specimens from the peak load to the ultimate load is more uniform, and it has excellent seismic performance. The average yield strength ratio of all specimens is 0.803, indicating that the structure has relatively good deformation space in the process of bearing load.

[0071] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A green self-compacting polymer concrete, characterized in that: Including the following raw materials by mass: 403-497 parts of cementitious materials, 178.02-226.98 parts of alkali activator solution, 618-636 parts of machine-made sand, 927-954 parts of crushed stone, 48.79-94.09 parts of added water, 18-36 parts of water reducing agent solution, and 13.5-22.5 parts of retarder; the cementitious materials include calcined copper tailings powder, slag and fly ash.

2. The green self-compacting polymer concrete according to claim 1, characterized in that: The mass fraction of the calcined copper tailings powder is 27-54 parts, the mass fraction of the slag is 216-243 parts, and the mass fraction of the fly ash is 160-200 parts.

3. The green self-compacting polymer concrete according to claim 2, characterized in that: The preparation method of the calcined copper tailings powder comprises: drying and grinding the copper tailings in sequence to obtain ground copper tailings; calcining the ground copper tailings to obtain the calcined copper tailings powder; The particle size of the ground copper tailings is not higher than 0.074 mm; The calcination temperature is 700-1000° C., the heat preservation time is 60-90 min, and the heating rate to the calcination temperature is 5-10° C. / min.

4. The green self-compacting polymer concrete according to claim 1 or 2, characterized in that: The modulus of the alkaline activator solution is 1 to 1.

4.

5. The green self-compacting polymer concrete according to claim 4, characterized in that: The preparation method of the alkaline activator solution comprises: adding a sodium hydroxide solution into a water glass solution to obtain the alkaline activator solution; the concentration of the sodium hydroxide solution is 10-14 mol / L.

6. The green self-compacting polymer concrete according to claim 5, characterized in that: The water glass solution has an initial modulus of 3.10-3.40, a solid content of 34%-36%, and a Baume degree of 38-41°Bé.

7. The green self-compacting polymer concrete according to claim 1 or 2, characterized in that: The machine-made sand is medium sand with a fineness modulus of 2.3-3.0; the crushed stone is natural crushed stone with a particle size of 5-16 mm; the fly ash is Class I fly ash with a particle size not higher than 0.074 mm; and the slag is Class S95 slag with a particle size not higher than 0.074 mm.

8. The green self-compacting polymer concrete according to claim 1 or 2, characterized in that: The water reducing agent solution is a polycarboxylic acid high-performance water reducing agent solution, the water reducing rate of the polycarboxylic acid high-performance water reducing agent solution is 26% to 30%, the air content is 4.0% to 5.5%, and the solid content is 38.5% to 41%; the retarder is sucrose.

9. The method for preparing the green self-compacting polymer concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mixing cementitious materials, crushed stone and machine-made sand to obtain a solid mixture; The solid mixture, alkali activator solution, water reducing agent solution, retarder and added water are mixed to obtain the green self-compacting polymer concrete.

10. A steel tube concrete column, characterized in that: It comprises a steel pipe and green self-compacting polymer concrete filled inside the steel pipe; The green self-compacting polymer concrete is the green self-compacting polymer concrete according to any one of claims 1 to 8 or the green self-compacting polymer concrete prepared by the preparation method according to claim 9.

Citation Information

Patent Citations

  • Geopolymer gel material based on copper tailings and preparation method of the material

    CN113173746A

  • Concrete filled steel tubular column and construction method thereof

    CN116427624A

  • Copper tailing-slag-based geopolymer for rigid concrete pavement and preparation process of copper tailing-slag-based geopolymer

    CN116444215A

  • Copper tailing geopolymer concrete as well as preparation method and application thereof

    CN118479802A

Cited By

  • Geopolymer cementing material prepared from diabase tailings and preparation method of geopolymer cementing material

    CN120829263A

  • Solid waste-based self-stress concrete filled steel tube and preparation method thereof

    CN121494426A